THE EFFECTIVENESS OF THE HEAT AND ITS TRANSFER E-MODULE BASED ON PROBLEM-BASED LEARNING TO IMPROVE STUDENTS' PROBLEM-SOLVING SKILLS - Euis Puspitasari; Baskoro Adi Prayitno; Lina Mahardiani (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The purpose of this study is to analyze the effectiveness of the e- modul of heat and its transfer based on Problem Based Learning (PBL) to improve the problem-solving skills of junior high school students who still have low skills. The research method used was quasi-experimental with a nonequivalent pretest-posttest control group design. The population used was seventh grade students at SMPN 2 Purwosari Bojonegoro. The sampling technique used was cluster random sampling. The research sample consisted of classes VIIA, VIIB, and VIIC with a total of 96 students.The research instrument was form of a problem-solving skills test consisting of 5 description questions. The sampling technique uses random sampling in which. The data analysis technique was used ANCOVA test and N-Gain score analysis. The ANCOVA results test is obtained a significance value of 0.000<0.05. This data shows that the use of e-modules has a significant influence on students' problem-solving skills. Based on the N-Gain score, were clearly showed that the use of e-modules provided higher improvement in problem-solving skills than the PPT in experiment class in the control class. The e-module class obtained a score of 0.31 (Identify), 0.52 (Define), 0.56 (Explore Strategies), 0.71 (Anticipate), and 0.76 (Look Back). Three indicators were in the medium category, and two indicators were in the high category. In contrast, control class reaches the low to medium category, and the control class is mostly in the low category. Based on this data, it can be concluded that the use of the heat and its transfer e-module based on PBL has proven to be effective in improving the problem-solving skills of junior high school students and helping students better understand concepts, as well as training them to think critically and reflectively.